Genome assembly of the Australian black tiger shrimp (Penaeus monodon) reveals a novel fragmented IHHNV EVE sequence. Issue 4 (10th February 2022) - Huerlimann, Roger; Cowley, Jeff A; Wade, Nicholas M; Wang, Yinan; Kasinadhuni, Naga; Chan, Chon-Kit Kenneth; Jabbari, Jafar S; Siemering, Kirby; Gordon, Lavinia; Tinning, Matthew; Montenegro, Juan D; Maes, Gregory E; et al.
Abstract: Shrimp are a valuable aquaculture species globally; however, disease remains a major hindrance to shrimp aquaculture sustainability and growth. Mechanisms mediated by endogenous viral elements have been proposed as a means by which shrimp that encounter a new virus start to accommodate rather than succumb to infection over time. However, evidence on the nature of such endogenous viral elements and how they mediate viral accommodation is limited. More extensive genomic data on Penaeid shrimp from different geographical locations should assist in exposing the diversity of endogenous viral elements. In this context, reported here is a PacBio Sequel-based draft genome assembly of an Australian black tiger shrimp ( Penaeus monodon ) inbred for 1 generation. The 1.89 Gbp draft genome is comprised of 31, 922 scaffolds (N50: 496, 398 bp) covering 85.9% of the projected genome size. The genome repeat content (61.8% with 30% representing simple sequence repeats) is almost the highest identified for any species. The functional annotation identified 35, 517 gene models, of which 25, 809 were protein-coding and 17, 158 were annotated using interproscan. Scaffold scanning for specific endogenous viral elements identified an element comprised of a 9, 045-bp stretch of repeated, inverted, and jumbled genome fragments of infectious hypodermal and hematopoietic necrosis virus bounded by a repeated 591/590 bp host sequence. As only near complete linear ∼4 kb infectious hypodermal and hematopoietic necrosis virus genomes have been found integrated in the genome of P. monodon previously, its discovery has implications regarding the validity of PCR tests designed to specifically detect such linear endogenous viral element types. The existence of joined inverted infectious hypodermal and hematopoietic necrosis virus genome fragments also provides a means by which hairpin double-stranded RNA could be expressed and processed by the shrimp RNA interference machinery.